Expression control of nitrile hydratase and amidase genes in Rhodococcus erythropolis and substrate specificities of the enzymes - Rucká, Lenka; Volkova, Olga; Pavlík, Adam; Kaplan, Ondřej; Kracík, Martin; Nešvera, Jan; Martínková, Ludmila; Pátek, Miroslav (Antonie van Leeuwenhoek, 2014)
Bacterial amidases and nitrile hydratases can be used for the synthesis of various intermediates and products in the chemical and pharmaceutical industries and for the bioremediation of toxic pollutants. The aim of this study was to analyze the expression of the amidase and nitrile hydratase genes of Rhodococcus erythropolis and test the stereospecific nitrile hydratase and amidase activities on chiral cyanohydrins. The nucleotide sequences of the gene clusters containing the oxd (aldoxime dehydratase), ami (amidase), nha1, nha2 (subunits of the nitrile hydratase), nhr1, nhr2, nhr3 and nhr4 (putative regulatory proteins) genes of two R. erythropolis strains, A4 and CCM2595, were determined. All genes of both of the clusters are transcribed in the same direction. RT-PCR analysis, primer extension and promoter fusions with the gfp reporter gene showed that the ami, nha1 and nha2 genes of R. erythropolis A4 form an operon transcribed from the Pami promoter and an internal Pnha promoter. The activity of Pami was found to be weakly induced when the cells grew in the presence of acetonitrile, whereas the Pnha promoter was moderately induced by both the acetonitrile or acetamide used instead of the inorganic nitrogen source. However, R. erythropolis A4 cells showed no increase in amidase and nitrile hydratase activities in the presence of acetamide or acetonitrile in the medium. R. erythropolis A4 nitrile hydratase and amidase were found to be effective at hydrolysing cyanohydrins and 2-hydroxyamides, respectively.
Keywords: genetická transkripce; DNA bakterií; dehydratasy; Substrate Specificity; Sequence Analysis, DNA; Transcription, Genetic; Hydro-Lyases; amidohydrolasy; Rhodococcus; regulace genové exprese u bakterií; sekvenční analýza DNA; Hydroxylamines; nitrily; DNA, Bacterial; substrátová specifita; Amidohydrolases; stanovení celkové genové exprese; hydroxylaminy; Gene Expression Regulation, Bacterial; Nitriles; Gene Expression Profiling; multigenová rodina; Multigene Family